Exploration on students’ understanding layers in solving arithmagon problems - Cholis Sa'dijah; Sri Rahayuningsih; Sukoriyanto Sukoriyanto; Abd. Qohar (LPMPP Universitas Negeri Yogyakarta, 2022)
The research aims at exploring the characteristics of ‘don’t need’ boundaries of students in solving arithmagon problems using qualitative descriptive approach. The participants win this research are 23 eight-grader junior high school students. The research used the instruments including test questions and unstructured interviews. The data collection procedure began with giving test questions to 23 participants. All of them could make mathematical diagrams/drawings/model precisely according to the information presented from the problem. The student who used effective and clear sentences in solving problems though could not solve the problem in a structured manner is called as Subject 1 (S1). The student who did not use effective and clear structured sentences is called as Subject 2 (S2). The student who used effective and clear sentences as well as structured in solving problems is called Subject 3 (S3). This research used triangulation method by exploring data obtained from the test and interview results. According to the research result, it is concluded that S1 crossed the first ‘don’t need’ boundaries when solving the addition and multiplication arithmagon problems. S2 crossed the first and second “don’t need” boundaries when solving addition arithmagon problem and only crossed the first ‘don’t need’ boundaries in solving multiplication arithmagon problems. However, S3 crossed the second ‘don’t need’ boundaries in solving arithmagon problem of addition and multiplication. Through this research, it is hoped that further research will be able to find and explore the third ‘don’t need’ boundaries in solving mathematical problems.